Conductometric Studies of Potassium Thiocyanate in 2-Propanol + Water Mixtures - Shivakumar, H.R.; N. Antony, Siju (Asian Journal of Chemistry, 2010)
Conductometric behaviour of the solutions of potassium thiocyanate in water and 2-propanol + water solvent mixtures have been investigated at varying conditions. Conductivity data were analyzed by Debye-Huckel-Onsager, Kraus-Bray and Shedlovsky models and used to evaluate limiting molar conductance, association constant, dissociation constant and Walden product for different compositions. The limiting molar conductance lmº sharply decreased with the increase in 2-propanol. Walden product (lm°h) is found maximum at x2pr (mole fraction of 2-propanol) = 0.0257 for 2-propanol + water solvent mixtures. Born relations were used to compute thermodynamics of solvation. Conductometric investigations revealed the structure breaking property of K+ ion. The results obtained from the study were used to interpret ion-ion and ion-solvent interactions.